Comparison of pulsar positions from timing and very long baseline astrometry - Wang, J.; Coles, W.; Hobbs, G.; Shannon, Ryan; Manchester, R.; Kerr, M.; Yuan, J.; Wang, N.; Bailes, M.; Bhat, N.; Dai, S.; Dempsey, J.; et al. (Oxford University Press, 2017)
Pulsar positions can be measured with high precision using both pulsar timing methods and very long baseline interferometry (VLBI). Pulsar timing positions are referenced to a solar-system ephemeris, whereas VLBI positions are referenced to distant quasars. Here, we compare pulsar positions from published VLBI measurements with those obtained from pulsar timing data from the Nanshan and Parkes radio telescopes in order to relate the two reference frames. We find that the timing positions differ significantly from the VLBI positions (and also differ between different ephemerides). A statistically significant change in the obliquity of the ecliptic of 2.16 ± 0.33 mas is found for the JPL ephemeris DE405, but no significant rotation is found in subsequent JPL ephemerides. The accuracy with which we can relate the two frames is limited by the current uncertainties in the VLBI reference source positions and in matching the pulsars to their reference source. Not only do the timing positions depend on the ephemeris used in computing them, but also different segments of the timing data lead to varying position estimates. These variations are mostly common to all ephemerides, but slight changes are seen at the 10 μas level between ephemerides.